2020 International Conference on Intelligent Systems and Computer Vision (ISCV) 2020
DOI: 10.1109/iscv49265.2020.9204099
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of COVID19 by deep learning transfer Model for populations in isolated rural areas

Abstract: To combat the spread of COVID 19, the World Health Organization suggests a large-scale implementation of COVID 19 tests. Unfortunately, these tests are expensive and cannot be provided and available for people in rural and remote areas. To remedy this problem, we will develop an intelligent clinical decision support system (SADC) for the early diagnosis of COVID 19 from chest x-rays which are more accessible for people in rural areas. Thus, we collected a total of 566 radiological images classified into 3 clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Another obstacle faced by health organizations is the speed of obtaining the outcomes of the test, which usually ranges from hours to days [ 46 , 47 ]. The lack of accurate and fast disease detection approach can cause patients to spread the disease to the community without knowing that they are infected [ 48 ]. Furthermore, patients who require urgent medical care might not get suitable therapy at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…Another obstacle faced by health organizations is the speed of obtaining the outcomes of the test, which usually ranges from hours to days [ 46 , 47 ]. The lack of accurate and fast disease detection approach can cause patients to spread the disease to the community without knowing that they are infected [ 48 ]. Furthermore, patients who require urgent medical care might not get suitable therapy at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…And the results indicated that the model achieved an accuracy of 92.00% in the multi-classification (COVID-19, pneumonia, and healthy chest X-ray images) and achieved an accuracy of 93.50% when distinguishing between COVID-19 chest X-ray images and non-COVID chest X-ray images. Qjidaa et al [119] adopted an ensemble classification method for COVID-19 diagnosis. They chose VGG16, VGG19, DenseNet121, MobileNet, Xception, InceptionV3, and InceptionResNetV2 to train, and each network produced a prediction.…”
Section: Covid-19 Diagnosis Based On Ensemble Learningmentioning
confidence: 99%
“…Hal ini tentu menyebabkan delay waktu yang cukup lama untuk mengetahui hasil laboratorium. Belum lagi pengiriman yang memerlukan waktu yang cukup lama memungkinkan specimen uji terkontaminasi sehingga meningkatkan risiko terjadinya false negativity result [4]. Ketiga, hambatan pelaksanaan testing Covid-19 secara masif berasal dari sisi pasien suspect sendiri.…”
Section: Pendahuluanunclassified